THE IMPACT OF AI IN THE FUTURE CAREERS (Ustozlar uchun, 2026)
This article provides an analytical overview of the transformative impact of artificial intelligence (AI) on human labor, employment dynamics, and the structure of the modern labor market. Empirical studies indicate that AI-driven automation will significantly alter workforce composition in sectors such as transportation, manufacturing, healthcare, and finance